Análisis del discurso de los personajes interpretados por Jaime Garzón en el programa televisivo de infoentretenimiento ‘Quac el Noticero’ en cadena uno, periodo 1995-1997 - Nancy Elizabeth, Diaz Zea (2021)
ABSTRACT Analysis of the speech of the characters performed by Jaime Garzón in the infoentertainment television program ‘Quac el Noticero’ in cadena uno, period 1995-1997 Autora: Nancy Elizabeth Diaz Zea Tutor: Msc. Vinicio Palacios In the 1990s, journalist Jaime Garzon, broadcast an infoentertainment program called ‘Quac El Noticero’, in which he analyzes drug trafficking, abuse of power, corruption and impunity within a social political context. Jaime Garzon with the desire to be a peace mediator for Colombia proposes the dissemination of a creative and critical space based on the current state of what is happening in the country. With a qualitative methodology, six leading actors are identified, through the analysis of the discourse their appearance and personality are described that also analyzes twelve sample episodes that Colombia maintains. The main objective is to give relevance and veracity to infoentertainment, counting on the performance of Jaime Garzon as a journalist who planted and created a television space for criticism and entertainment, setting a precedent, in the Colombian media, by showing an innovative way at the time of giving information, with a touch of humor and satire that spoke of really important issues in the country, reaching beyond a segmentation. KEY WORDS: Infotainment, discourse analysis, journalism, information, television. Reviewed by: Danilo Yépez Oviedo English professor UNACH 0601574692